Effect of High-iron Rice Intervention on VO2max of Female Students of Al-Falak Bogor Islamic Boarding School: PENGARUH INTERVENSI BERAS TINGGI BESI TERHADAP VO2MAX SANTRIWATI PONDOK PESANTREN AL-FALAK BOGOR - Ade Salma Yunia Rachmah; Mira Dewi; Evy Damayanthi; Dwinita Wikan Utami (Universitas Airlangga, 2022)
Female adolescents are at risk of iron deficiency which is known can negatively affect fitness. High-iron rice has been developed through biofortification but there is still lack of evidence regarding its benefit in improving VO2max as a physical fitness indicator. This study aimed to determine impact of high-iron rice intervention towards VO2max value. A total of 18 female students from Al-Falak Bogor Islamic boarding school aged 12-18 years were selected purposively in this quasi-experimental study. High-iron rice contained 50.4 ppm iron provided thrice daily for 4 weeks. A 20 m shuttle run test was conducted to obtain VO2max value. Other data such as food intake, BMI for age, hemoglobin, and serum ferritin were also evaluated. Paired t-test or Wilcoxon Ranks test was performed to analyze difference in data value before and after the intervention. Most nutrient intakes experienced a significant decline (p<0.05) after the intervention, except for iron intake. Hemoglobin concentration also became lower significantly, whereas serum ferritin did not alter significantly. Nevertheless, VO2max improved significantly after the intervention. To summarize, there was an increase in fitness after high-iron rice intervention for 4 weeks in female students.